Automated informed consent - Andreotta, Adam John; Lundgren, Björn (Big Data & Society, 2024)
Online privacy policies or terms and conditions ideally provide users with information about how their personal data are being used. The reality is that very few users read them: they are long, often hard to understand, and ubiquitous. The average internet user cannot realistically read and understand all aspects that apply to them and thus give informed consent to the companies who use their personal data. In this article, we provide a basic overview of a solution to the problem. We suggest that software could allow users to delegate the consent process and consent could thus be automated. The article investigates the practical feasibility of this idea. After suggesting that it is feasible, we develop some normative issues that we believe should be addressed before automated consent is implemented.
CRIS-Team Scopus Importer:2025-02-04
Keywords: automated consent; consent forms; ethics; Informed consent; privacy policy

On the need for a global AI ethics - Lundgren, Björn; Catena, Eleonora; Robertson, Ian; Hellrigel-Holderbaum, Max; Jaja, Ibifuro; Dung, Leonard (Journal of Global Ethics, 2024)
The impact of artificial intelligence (AI) is not only global but globally varied. Yet, AI ethics is all too often overly localised. This paper discusses the potential of a global AI ethics, highlighting several important variables that it should take into account if it is to be as successful an enterprise as it needs to be.
CRIS-Team Scopus Importer:2024-12-13
Keywords: AI ethics; AI guidelines; global AI ethics; international relations; technological disparities

There is No Scarcity Problem - Lundgren, Björn (Philosophy & Technology, 2024)
Recently, John Danaher and Sven Nyholm argued that partial “digital duplicates” of real persons (simulations and imitations) prima facie makes the real person less valuable because they become less scarce. They call this the “scarcity problem.” If true, this thesis is amongst the most important insights in ethics of technology because of the simplicity of duplication. However, based on an analysis of their argument, I suggest that the thesis has no support.
CRIS-Team Scopus Importer:2024-11-29
Keywords: AI; Digital duplicate; Non-replaceability; Scarcity; Value

Undisruptable or stable concepts: can we design concepts that can avoid conceptual disruption, normative critique, and counterexamples? - Lundgren, Björn (Ethics and Information Technology, 2024)
It has been argued that our concepts can be disrupted or challenged by technology or normative concerns, which raises the question of whether we can create, design, engineer, or define more robust concepts that avoid counterexamples and conceptual challenges that can lead to conceptual disruption. In this paper, it is argued that we can. This argument is presented through a case study of a definition in the technological domain.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Conceptual counterexamples; Conceptual disruption; Conceptual engineering; Normative critique of concepts; Stable concepts; Undistruptable concepts

What we owe (to) the present: Normative and practical challenges for strong longtermism - Lundgren, Björn; Kudlek, Karolina (Futures, 2024)
This paper critically examines the conceptual, normative, and practical challenges to strong longtermism—the view that the far future is the key priority in moral decision-making. The main challenge is that if we take strong longtermism seriously, it follows that harming present and near-future people is permissible, if not obligatory. Given that this conclusion is repugnant to most, we argue that strong longtermism must be substantially weakened. Furthermore, even if strong longtermists bite the bullet on the challenge of what we owe to the present, we raise a set of related concerns that demand attention. Specifically, we argue that it is questionable whether the far future can be a difference-maker in moral decision-making. Even if it could, our inability to predict or understand how the far future will unfold, or what values future generations will hold, severely limits our capacity to account for it. Finally, the implementation of strong longtermism requires a level of progressive moral reasoning that far exceeds our current cognitive and ethical capabilities. While these objections do not necessarily debunk strong longtermism, they seriously challenge its plausibility—as it currently stands.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Future values; Longtermism; Moral change; Moral psychology; Strong longtermism; Uncertainty